Comparative Assessment of Quality Management System in Selected Housing Construction Projects in Lalitpur District - Lakhey, Sanam; Tuladhar, Amrit Man (Journal of UTEC Engineering Management, 2023)
The objective of the study was to assess the quality management system applied in housing construction projects of Lalitpur district. General questionnaire survey on quality management system was done in ten housing developers. Detail assessment on quality management system was done only in two housing projects i.e. CE housing and Civil homes housing. This research was based on key informant interview with project manager and site engineers, questionnaires survey with clients, consultants and contractors who were involved in building construction projects. Statistical tools mean value and relative importance index were used for the ranking of different quality methods. The importance of the individual factor are calculated and ranked by their relative importance index (RII). Total Quality Management, Quality Management system and Quality control ranked highest respectively as a part of quality management process employed in the project. From the study, it was found that different stakeholders have different priorities and preferences. Clients give major priority to procurement of equipment and material. Consultants give main priority to recorded outcomes and achievement and contractors give management commitment and involvement as main priority. Training and education in quality, work improvement teams, customer expectations are found as important. The outcome of this thesis will document the quality management system and will also assist to improve the quality system of housing construction in Lalitpur districts. Proper documentation regarding quality control should be maintained at site. For ensuring optimum quality management in housing projects, timely ISO audits system should be set up.